Experimental investigation of pulsating heat pipe performance with regard to fuel cell cooling application - Clement, Jason; Wang, Xia (Applied thermal engineering, 2013)
A pulsating heat pipe (PHP) is a closed loop, passive heat transfer device. Its operation depends on the phase change of a working fluid within the loop. Design and performance testing of a pulsating heat pipe was conducted under conditions to simulate heat dissipation requirements of a proton exchange membrane (PEM) fuel cell stack. Integration of pulsating heat pipes within bipolar plates of the stack would eliminate the need for ancillary cooling equipment, thus also reducing parasitic losses and increasing energy output. The PHP under investigation, having dimensions of 46.80 cm long and 14.70 cm wide, was constructed from 0.3175 cm copper tube. Heat pipes effectiveness was found to be dependent upon several factors such as energy input, types of working fluid and its filling ratio. Power inputs to the evaporator side of the pulsating heat pipe varied from 80 to 180 W. Working fluids tested included acetone, methanol, and deionized water. Filling ratios between 30 and 70 percent of the total working volume were also examined. Methanol outperformed other fluids tested; with a 45 percent fluid fill ratio and a 120 W power input, the apparatus took the shortest time to reach steady state and had one of the smallest steady state temperature differences. The various conditions studied were chosen to assess the heat pipe's potential as cooling media for PEM fuel cells. ► Methanol as a working fluid outperformed both acetone and water in a pulsating heat pipe. ► Performance for the PHP peaked with methanol and a fill ratio of 45 percent fluid to total volume. ► A smaller resistance was associated with a higher power input to the system.